TAXONOMY OF EDUCATIONAL OBJECTIVES OF EDUCATORS AND PARENTS OF PRESCHOOL CHILDREN IN THE CONTEXT OF THE REQUIREMENTS OF THE FEDERAL STATE EDUCATIONAL STANDARD - V. B. Veretennikova; O. F. Shikhova; Yu. A. Shikhov (Obrazovanie i Nauka, 2016)
The purpose of the article is to describe the taxonomic model thatallows diagnosing the levels of formation of the basic competencies of educators and parents in the conditions of realization of the federal state educational standard in preschool organizations. Methods. The methods of the research are based on qualimetric and competence approaches, which assume pedagogical expertise of the structure, content and levels of formation of basic competencies of subjects of educational process in the system of preschool education.Results. The need of formation of basic competences of teachers of the preschool educational institutions (PEI) and parents of the kindergarten children is proved. It is shown how this process has to be reproduced in the individual educational routes directed to creation of optimum conditions for development of the child of early age.Scientific novelty. A multi-functional taxonomic model of competencies formation among teachers and parents is proposed. This model reflects competenceoriented educational objectives of the members of educational process in preschool education, and makes it possible to examine the extent of its achievement.Practical significance. Presented in the article taxonomic model can be used in the system of retraining and advanced training of educators of preschool organizations, as well as training of parents of preschool children to the implementation of the Federal State Educational Standard of preschool education.